Contributions of psychology to war and peace - Montiel, Cristina Jayme (Archīum Ateneo, 2013)
The contributions of American psychologists to war have been substantial and responsive to changes in U.S. national security threats and interests for nearly 100 years. These contributions are identified and discussed for four periods of armed conflict: World Wars I and II, the Cold War, and the Global War on Terror. In contrast, about 50 years ago, largely in reaction to the threat of nuclear war, some psychologists in the United States and around the world broke with the tradition of supporting war and began focusing their scholarship and activism on the prevention of war and promotion of peace. Today, peace psychology is a vibrant area of psychology, with theory and practice aimed at understanding, preventing, and mitigating both episodes of organized violence and the pernicious worldwide problem of structural violence. The growth, scope, and content of peace psychology are reviewed along with contributions to policies that promote peace, social justice, and human well-being.